Approach to Higher Wheat Yield in the Huang-Huai Plain: Improving Post-anthesis Productivity to Increase Harvest Index - Duan, Jianzhao; Wu, Yapeng; Zhou, Yi; Ren, Xingxu; Shao, Yunhui; Feng, Wei; Zhu, Yunji; He, Li; Guo, Tiancai (Frontiers in Plant Science, 2018)
Both increased harvest index (HI) and increased dry matter (DM) are beneficial to yield; however, little is known about the priority of each under different yield levels. This paper aimed to determine whether HI or DM is more important and identify the physiological attributes that act as indicators of increased yield. Two field experiments involving different cultivation patterns and water - nitrogen modes, respectively, were carried out from 2013-2016 in Huang-Huai Plain, China. Plant DM, leaf area index (LAI) and radiation interception (RI) were measured. Increased yield under low yield levels < 7500 kg ha-1 was attributed to an increase in both total DM and HI, while increases under higher yield levels > 7500 kg ha-1 were largely dependent on an increase in HI. Under high yield levels, HI showed a significant negative correlation with total DM and a parabolic relationship with net accumulation of DM during filling. Higher net accumulation of DM during filling helped slow down the decrease in HI, thereby maintaining a high value. Moreover, net DM accumulation during filling was positively correlated with yield, while post-anthesis accumulation showed a significant linear relationship with leaf area potential (LAP, R2 =0.404-0.526) and radiation interception potential (RIP, R2 =0.452-0.576) during grain filling. These findings suggest that the increase in LAP and RIP caused an increase in net DM accumulation after anthesis. Under DM levels > 13,000 kg ha-1 at anthesis, maintaining higher LAI and RI in lower layers during grain formation contributed to higher yield. Furthermore, the ratio of upper- to lower-layer RI showed a second-order curve with yield during filling, with an increase in the optimal range with grain development. Pre-anthesis translocation amount, and the translocation and contribution ratios also showed second-order curves under high yield levels, with optimal values of 3000-4500 kg ha-1, 25-35 % and 30-50 %, respectively. These results confirm the importance of HI in improving yield, providing a theoretical basis for wheat production in the Huang-Huai Plain.